The Development of Students’ Worksheets Based on Combinatoric Reasons in Elementary School - Aini, Nurul; Suryowati, Eny (Universitas Muhammadiyah Mataram, 2024)
This study was motivated by the many shortcomings of students’ worksheets so far, including the incapability in developing students’ scientific skills and high-level thinking. Meanwhile, the learning objectives of the elementary school level get students to think reasonably and solve problems. Therefore, developing students’ worksheets based on combinatoric reason is the solution, as it drills students to have sustainable thinking. This study aimed to see the validity, practicality, and effectiveness of students’ worksheets based on combinatoric reason. It is a Research and Development study with the Plomp model. The plomp model consists of preliminary investigation; design; realization/construction; and test, evaluation, and revision. The research instruments were students’ worksheets, validation form, questionnaire, and test form. The subject involved 40 students in the sixth grade of elementary school. The data analysis used is descriptive qualitative and descriptive quantitative. It resulted in 91,5% for the validity (very valid), 90,9% for the practicality (very practical), and 92,5% for the effectiveness (very effective). Thus, it indicates that students’ worksheets based on combinatoric reason are valid, practical, and effective, which are proper for elementary school. So, it is recommended that mathematics teachers use it in learning, because it trains students to use combinatorial reasoning. As a result, students become flexible and logical in determining strategies, as well as being systematic in solving problems. As a result, elementary school students' Problem-solving and higher order thinking abilities become better.